Development of a lateral flow immunochromatography test for the rapid detection of bovine tuberculosis - Alonso, Maria Natalia (2021)
Detection of specific antibodies would be a useful test strategy for bovine tuberculosis (bTB) as a complement to the single skin test. We developed a lateral flow immunochromatography (LFIC) test for rapid bTB detection based on the use of a conjugate of gold nanoparticles with a recombinant G protein. After evaluating 3 Mycobacterium bovis (MB) antigens: ESAT-6, CFP-10 and MPB83 for the control line, we selected MPB83 given it was the most specific. The performance of the test was analyzed with 820 bovine sera, 40 sera corresponding to healthy animals, 5 sera from animals infected with Mycobacterium avium subsp. paratuberculosis (MAP) and 775 sera of animals from herds with bTB. All these sera were also submitted to a validated bTB-ELISA using whole-cell antigen from MB. From the 775 sera of animals from herds with bTB, 87 sera were positive by the bTB-ELISA, 45 were positive by LFIC and only 5 animals were positives by skin test (TST). To confirm bTB infection in the group of TST (−), bTB-ELISA (+) and LFIC (+) animals, we performed postmortem examination in 15 randomly selected animals. Macroscopically, these 15 animals had numerous small and large yellow-white granulomas, characteristic of bTB, and the infection was subsequently confirmed by PCR in these tissues with lesions (gold standard). No false positive test result was detected with the developed LFIC either with the sera from healthy animals or from animals infected with MAP demonstrating that it can be a useful technique for the rapid identification of animals infected with bTB.